Analysis of the Effect of Marketing Mix 7P on Purchase Decisions at Sentra Snack Stores - Ivana Tanjung (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
This study examines the analysis of marketing mix (7P) effect to buying decision at Sentra Snack Store. Marketing mix (7P) are product, price, place, and promotion, people, process, and physical evidence. The main theory used is Theory of Reasoned Action by Fishbein and Ajzen (1975). The method used by this research is a quantitative research method, where the data is measured numerically and used Structural Equation Modeling with Partial Least Square. Theprogram used SmartPLS 3.3.3. The research was held at Sentra Snack Store, located in Surabaya with seventy samples of Sentra Snack Store customers. The results are Product and Price have a significant effect to Buying Decisions at Sentra Snack Store, while Promotion, Place, People, Process, and Physical Evidence do not. These results can be used as a basis for developing related strategies because they will further affect the company's sales and profit turnover.